Effectiveness of Blended Learning for Students in the Office Administration Education Study Program, Faculty of Social Sciences and Law, Makassar State University - Andi Artika Melati; Sirajuddin Saleh; Isgunandar (Journal of Educational Development and Learning (JEDAL), 2024)
Blended learning is a learning method that combines face-to-face and virtual learning which can help students learn more flexibly, variedly and produce better understanding, because students can learn without being limited by distance, space and time. Makassar State University is one of the campuses that implements blended learning-based learning, which is supported by the release of the SYAM-OK learning platform. With this, the research objective to be achieved is to determine the effectiveness of blended learning-based learning for students of the Office Administration Education Study Program, Faculty of Social Sciences and Law, Makassar State University. This research is descriptive qualitative research. The results of this research show that the effectiveness of the application of blended learning in the Office Administration Education Study Program, when viewed as a whole, is effective. This can be seen from the research results for each indicator, namely: 1) Blended learning-based learning planning, including the policy of 70% face-to-face and 30% virtual face-to-face learning based on blended learning, as well as all the thorough preparations carried out by lecturers and students before implementing based learning. blended learning 2) Implementation of Blended Learning Based Learning, including, the role of lecturers and students in blended learning based learning, use of appropriate media, strategies and learning methods by lecturers, as well as maximum use of the learning platforms that have been provided, and 3) Evaluation of Based Learning Blended learning, including the assessment system used by lecturers to measure students' level of understanding in blended learning-based learning, the form of evaluation given by lecturers to students, as well as student learning outcomes which tend to be good after implementing blended learning-based learning.